2018
DOI: 10.1186/s12920-018-0407-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glioblastoma gene prognosis modules based on weighted gene co-expression network analysis

Abstract: BackgroundGlioblastoma multiforme, the most prevalent and aggressive brain tumour, has a poor prognosis. The molecular mechanisms underlying gliomagenesis remain poorly understood. Therefore, molecular research, including various markers, is necessary to understand the occurrence and development of glioma.MethodWeighted gene co-expression network analysis (WGCNA) was performed to construct a gene co-expression network in TCGA glioblastoma samples. Gene ontology (GO) and pathway-enrichment analysis were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 37 publications
(37 reference statements)
1
37
0
Order By: Relevance
“…Similarly, SPTA1 (Spectrin, alpha, erythrocytic 1) mutations can led to alterations in H&E-stained tissue features due to its involvement in the regulation of cortical actin organization and cell shape as it has been shown in other cancers [57], although its role in GBM has not been investigated yet. Similar conclusions in relation to the tumour microenvironment and the differential expression of extracellular matrix (ECM) proteins (and therefore outside-in cell-ECM signalling) have been identified to be highly and inversely correlated to patient's survival rates [58]. Thus, these observations suggest that differences in the cellular and noncellular microenvironment [10] and the way that cancer cells sense it through adhesion receptors and modulation of the actin cytoskeleton (i.e.…”
Section: Gene Mutation Frequency Within Survival Classesmentioning
confidence: 55%
“…Similarly, SPTA1 (Spectrin, alpha, erythrocytic 1) mutations can led to alterations in H&E-stained tissue features due to its involvement in the regulation of cortical actin organization and cell shape as it has been shown in other cancers [57], although its role in GBM has not been investigated yet. Similar conclusions in relation to the tumour microenvironment and the differential expression of extracellular matrix (ECM) proteins (and therefore outside-in cell-ECM signalling) have been identified to be highly and inversely correlated to patient's survival rates [58]. Thus, these observations suggest that differences in the cellular and noncellular microenvironment [10] and the way that cancer cells sense it through adhesion receptors and modulation of the actin cytoskeleton (i.e.…”
Section: Gene Mutation Frequency Within Survival Classesmentioning
confidence: 55%
“…WGCNA is a powerful tool for analysing multiple genes in large-scale datasets. It has been extensively used to explore gene co-expression modules and hub genes as potential target biomarkers in many cancers (Foroughi et al, 2018;Chen et al, 2018;Giulietti et al, 2016;Liu et al, 2019;Wang et al, 2019a;Wang et al, 2019b;Xu et al, 2018;Zhai et al, 2019;Zhang et al, 2019a;Zhang et al, 2019b;Zhang et al, 2019c). In the current study, we applied WGCNA and systematically identified the turquoise module as the most significantly negatively associated (r = −0.2, P = 4e−04) with pathologic stage for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…The association between the polymorphism of OSMR gene and bladder cancer was determined, which would affect the recurrence rate, overall survival and tumor grade [17]. Xu et al have discovered that OSMR might be a prognostic biomarker in glioblastoma and overexpression of OSMR can regulate the immune response of glioblastoma [18,19].…”
Section: Discussionmentioning
confidence: 99%